Chapter 1 Historical Organization Studies Advancing new direction for organizational research - Maclean, Mairi (Taylor & Francis, 2021)
We are now entering a new phase in the establishment of historical organization studies as a distinctive methodological paradigm within the broad field of organization studies. This book serves both as a landmark in the development of the field and as a key reference tool for researchers and students. For two decades, organization theorists have emphasized the need for more and better research recognizing the importance of the past in shaping the present and future. By historicizing organizational research, the contexts and forces bearing upon organizations will be more fully recognized and analyses of organizational dynamics improved. But how, precisely, might a traditionally empirically-oriented discipline like history be incorporated into a theoretically-oriented discipline like organization studies? This book evaluates the current state of play, moves it on and identifies the possibilities the new emergent field offers in the future. In addition to providing important reference to the subject for researchers, the book can be used to introduce management and organizational history to a student audience at both undergraduate and postgraduate levels. The book is a valuable source for wider reading, providing rich reference material in tutorials across organizational studies, or as recommended or required reading on courses with a connection to business or management history.